On Solving the Equilibrium Problem and Fixed Point Problem for Nonspreading Mappings and Lipschitzian Mappings in Hilbert Spaces: Sarawut Suwannaut - Team, Support (Thai Journal of Mathematics, 2019)
The purpose of this research is to introduce and study the S-mapping generated by a finite family of nonspreading mappings and Lipschitzian mapping in a Hilbert space. Then, we prove a strong convergence theorem for finding a common element of the set of fixed points of a finite family of nonspreading mappings and Lipschitzian mappings and a common solution of a finite family of equilibrium problems. Futhermore, applying our main theorem, the additional results for equilibrium problem are obtained.